A Case Study Primer: Origins and Basic Principles (Global Journal of Human-Social Science, 2017)
Case studies are a highly utilized methodology in the field of qualitative research. The case study approach is appealing to researchers across the continuum from beginners to experts. Unlike quantitative data that focuses upon numerical implications and statistics, case studies allow the researcher to use various observational tools to collect indepth data about a given research inquiry. This data collection tends to focus on a single case or group, and often includes a more human or behavioral sense of direction within the confines of the research setting. Case study practitioners also wish to see the interaction of subjects within this research setting, as opposed to treating these subjects as wholly individualized entities.
Keywords: case study; qualitative research; researcher; case study basics; case study origins